Paper star - Hayes, Mary-Rose (New York : Dutton, 1991)
Fast-paced, seductive and thoroughly engrossing story of four friends who set out to conquer Hollywood with youthful gutsiness and raw talent - and nearly lose their dreams on the dark side of the glamorous town.
National College of Business and Arts
Keywords: Love stories